Contentious and Advisory Jurisdiction of the International Tribunal for the Law of the Sea. - García-Revillo, Miguel García (Brill, 2015)
In The Contentious and Advisory Jurisdiction of the International Tribunal for the Law of the Sea, Miguel García García-Revillo offers an in depth examination of both the contentious and advisory jurisdiction of this major international judicial institution.--